Revision and Multiple Validity Verification of Self-Presentation Skills Assessment for Middle School Students - Tong, Weiwei; Saihong, Prasong; Sonsupap, Kanyarat (International Journal of Language Education, 2024)
The main objective of this study is to revise and validate the assessment of self-presentation skills of middle school students. The assessment is based on existing self-assessment scales and adaptively modified for a more accurate assessment of middle school students' self-presentation skills. Considering the characteristics of middle school students and teachers' assessment, we have reconstructed and adjusted the dimensions of the original assessment. This paper includes background research, scale design and innovation, scale testing, and scale reliability and multiple validity verification. In order to further verify the effectiveness and reliability of the tool, this study added the application of content validity and factor analysis on the basis of previous studies. The results of this study are intended to compensate for the limitations of current teacher assessment for middle school students' self-presentation. At the same time, this study also provides a basis for the development of middle school students' self-presentation skills integrated training programs.